Making meaningful connections: using insights from social pedagogy in statutory child and family social work practice. Issue 2 (7th November 2016) - Ruch, Gillian; Winter, Karen; Cree, Viv; Hallett, Sophie; Morrison, Fiona; Hadfield, Mark
Abstract: Reports into incidents of child death and serious injury have highlighted consistently concern about the capacity of social workers to communicate skilfully with children. Drawing on data collected as part of an Economic and Social Research Council funded UK‐wide research project exploring social workers' communicative practices with children, this paper explores how approaches informed by social pedagogy can assist social workers in connecting and communicating with with children. The qualitative research included data generated from 82 observations of social workers' everyday encounters with children. Social pedagogical concepts of 'haltung' (attitude), 'head, heart and hands' and 'the common third' are outlined as potentially helpful approaches for facilitating the intimacies of inter‐personal connections and enhancing social workers' capacity to establish and sustain meaningful communication and relationships with children in the face of austere social, political and organisational contexts.